Game development tools - Ansari, Marwan (CRC Press, 2011)
"This book brings the insights of game professionals, DCC creators, hardware vendors, and current researchers together into a collection that focuses on the most underrepresented and critical part of game production: tools development. The first gems-type book dedicated to game tools, this volume focuses on practical, implementable tools for game development professionals. Topics range from asset tracking to improving remote version control performance to robust and efficient IO. Technical artists, as well as game play, audio, and graphics programmers will find new tools to improve work flow and help build games faster"-- Provided by publisher